Analysis Level of Satisfaction Student P3d for Distance Learned Based End-User Computing Satisfaction (Eucs) Method in the COVID-19 Era - Anita Merry Cisca; Sri Wahyuni Nasution; Sri Lestari Ramadhani Nasution; Ermi Girsang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This work aims to investigate an Indonesian EFL student’s perceptions and experiences in repeatedly doing standardized English language proficiency test: TOEIC (Test of English for International Communication) and TOEFL (Test of English as a Foreign Language). This standardized test has a significant role in the academic and professional lives of students (Anam, 2019); it contributes positively to students’ language proficiency and their future employment if they have higer and valid score in the test (Hsieh, 2017). This present study interviewed an Indonesian EFL student at a National University in Taiwan running an international program. The study participant passed the exam, but she did it repeatedly before she could pass it. This study used a qualitative phenomenological approach with an in-depth interview. The relevant findings illustrate that the participant reveals the reasons for failing the test: lack of self-awareness, lack of self-confidence, and the distance of the test venue from her dormitory. On the contrary, she passed the test by doing online simulation exam individually and modifying her study skills while preparing for the test. The failure process had a positive impact on her in making her to know her ability.